The Hydroacoustic Component of an International Monitoring System - Schrodt, Joseph K.; Clauter, Dean a.; Schult, Frederick R. (1995)
The critical issue for the hydroacoustic component of an International Monitoring System (IMS) is its capability for monitoring nuclear explosions in the world's oceans. Factors that affect this capability are number and location of hydroacoustic sensors, placement of sensors, blockage of the hydroacoustic signal due to bathymetric effects, and spatial and temporal variation in hydroacoustic signal propagation due to changes in oceanic properties. This paper provides examples of hydroacoustic monitoring capability from historical data that demonstrates the impact of these factors, and discusses implications from these results on design of a hydroacoustic network. Specific data processing examples of hydroacoustic detection and discrimination capability are given for hydroacoustic signals from earthquakes and explosions recorded at MILS (Missile Impact Location System) and other hydrophones in the Atlantic and Pacific Ocean. In the 1960's, the United States (U.S.) Navy performed a series of ship sinking explosions underwater as well as a set of explosions that traversed the Aleutian Island chain at a ninety degree angle. Another study is of more recent data from a collection of earthquakes south of Australia and in the Southern Pacific Ocean also detected on MILS and other hydrophones. Examples from all of these data illustrate the blockage effects due to the bathymetric profile and effects of hydroacoustic sensor emplacement on the side or top of, or floated from the top of seamounts into the SOFAR channel on hydroacoustic signal strength. This article is from 'Proceedings of the Annual Seismic Research Symposium on Monitoring a Comprehensive Test Ban Treaty (17th) Held in Scottsdale, Arizona on 12-15 September, 1995', 1996 0607 035, p995.